SADNESS AMONG ADOLESCENTS IN DIFFERENT SOCIAL SETTINGS IN INDONESIA: AN INDIGENOUS PSYCHOLOGY STUDY - Dewi Anjarsari, Novita; Abdul Hakim, Moh.; W. Yuniarti, Kwartarini (Universitas Ahmad Dahlan, 2010)
Adolescence is a transition period filled with a state of storm and stress. These conditions contribute in increasing the level of adolescents´ unhappiness. Each adolescent has a different meaning of sadness depending on their belief. The previous studies stated that Indonesian had positive attitudes towards sad moments. The aim of this research was to discover the meaning of unhappiness among adolescents raised in large cities, rural and urban areas. A total of 426 senior high school students between 1417 years old (urban=151, rural=215, metropolitan=60), were asked to complete open-ended questionnaires by answering the question